(untitled) (Comunicação & Inovação, 2017)
The search for innovation has been incorporated in the production processes of modern enterprises to achieve increased competitiveness in the market. However, innovation cannot be seen only as an economic activity. Corporate communication is also important in developing innovative processes. This article analyzes the role and the relation between communication and innovation in the activity of Embraer with the program Desafio Innova, which encourages its employees, through communication, to create innovative solutions to its problems. Our theoretical framework is mainly based on researchers as North, Johnson-Laird and Allen. The conclusions of this article show that the program may be useful to other enterprises.